Influence of a virtual educational intervention on the maintenance of exclusive breastfeeding during the Covid-19 pandemic - González-Berrocal, Paula; Ortiz-Rodríguez, Irene (Enfermería Cuidándote, 2022)
General objective: To analyze the influence of a virtual educational intervention on the maintenance of Exclusive Breastfeeding at 6 months postpartum in women treated at the Maternal-Infant Hospital of Malaga during the COVID-19 pandemic. Methodology: Qualitative and quantitative mixed study in two phases. In the first, a focus group is held to find out the needs of breastfeeding mothers in our environment. In the second phase, a randomized clinical trial is developed in which a virtual educational intervention is compared with normal clinical practice. Scope and study population: Women cared for in the Maternity area of the Maternity and Infant Hospital of Malaga who meet the inclusion and exclusion criteria. Conclusion: The scenario during the Covid-19 pandemic is an opportunity to explore the needs, improve the experience of women, as well as increase the duration of exclusive breastfeeding up to 6 months, taking advantage of information and communication technologies.